Phylogenetic Analysis of Mystus species using 16S rRNA in Batang Kerang, Balai Ringin, Sarawak - Goh, Pei Tian (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Southeast Asian region has one of the highest diversity of freshwater fishes. Mystus spp. is one of the famous freshwater fish species but there were less research was done on this particular species. This species is regularly misidentified with other family member as they have similar appearance. Therefore this study not only investigated the phylogenetic relationship among the Mystus spp. by using the 16s rRNA sequence but also constructed phylogenetic trees for the Mystus spp. that can be found in Batang Kerang, Balai Ringin, Sarawak. The muscle tissues of the fishes were taken and their DNA was extracted by using Wizard Genomic DNA Purification Kit (Promega). The extracted DNA was undergoing PCR. The PCR product was observed by using gel electrophoresis and the DNA sequences were analysed using MEGA 6.06 software. Overall, the phylogenetic tree constructed showed the monophyletic relationship of the identified Mystus spp. that captured at Batang Kerang. The method used to analyse in this study were Neighbour Joining, Maximum Likelihood and Maximum Parsimony. The methods showed highly similar topography tree with similar bootstrap value. This showed that, the Mystus spp. at Batang Kerang is highly and closely related. The phylogenetic trees constructed also successful classified Mystus spp that capture at Balai Ringin into respective clades.